2018
DOI: 10.1371/journal.pntd.0006246
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of previous but not current transmission of chikungunya virus in southern and central Vietnam: Results from a systematic review and a seroprevalence study in four locations

Abstract: BackgroundArbovirus infections are a serious concern in tropical countries due to their high levels of transmission and morbidity. With the outbreaks of chikungunya (CHIKV) in surrounding regions in recent years and the fact that the environment in Vietnam is suitable for the vectors of CHIKV, the possibility of transmission of CHIKV in Vietnam is of great interest. However, information about CHIKV activity in Vietnam remains limited.MethodologyIn order to address this question, we performed a systematic revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
1
23
0
Order By: Relevance
“…The majority of the studies were exclusively conducted on dengue [ 15 112 ] (n = 123), with 16.% exclusively conducted on chikungunya (n = 29) [ 113 136 ] and 12% conducted on both dengue and chikungunya (n = 23) [ 137 154 ]; furthermore, seven studies were conducted on Zika [ 8 , 155 160 ], one study was conducted on both dengue and Zika [ 161 ] and two studies were conducted on both viruses [ 162 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of the studies were exclusively conducted on dengue [ 15 112 ] (n = 123), with 16.% exclusively conducted on chikungunya (n = 29) [ 113 136 ] and 12% conducted on both dengue and chikungunya (n = 23) [ 137 154 ]; furthermore, seven studies were conducted on Zika [ 8 , 155 160 ], one study was conducted on both dengue and Zika [ 161 ] and two studies were conducted on both viruses [ 162 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 2013, CHIKV emerged in the Americas, and in 2014 and 2015, five studies were conducted in the Caribbean [ 118 , 118 , 119 , 121 ] (Saint-Martin, Guadeloupe, Martinique and Puerto Rico) and Central America [ 122 ] (Nicaragua) during an outbreak in Saint Martin and post-outbreak in the other locations. One study was conducted in Vietnam in 2015, where little was known about CHIKV transmission and where dengue is endemic [ 136 ]. The last study was conducted in 2016 in Brazil in a post-outbreak context [ 128 ].…”
Section: Resultsmentioning
confidence: 99%
“…This disease and dengue fever are both transmitted by Aedes mosquitoes and have similar symptoms, which makes it easy to confuse these diseases and underrecognize chikungunya cases in dengue hyperendemic areas [40]. However, the most recent systematic review found no evidence of recently sustained transmission of chikungunya in central and southern Vietnam [41].…”
Section: Discussionmentioning
confidence: 99%
“…Under this consideration, it is somewhat logical that the model under predicts the incidence of dengue in 10-19-year-olds but over predicts its incidence in 20-59-year-olds. In future implementations, the model may be better able to replicate the age distribution of cases if it used a temporally-variable force of infection, similar to Quan et al (2018).…”
Section: Discussionmentioning
confidence: 99%